Producción del clon de cacao (Ttheobroma cacao lL.) CCN-51 orgánico a tres distanciamientos en un sistema triangular de doble hilera. Los Ríos, 2014 - Pacheco Sánchez, Eduardo Luis (2015)
The present study was conducted during the rainy season 2014, during the months of January to June, at the Experimental Farm "Dam" State Technical University of Quevedo (UTEQ) located on the premises Fayta, Kilometer 7.5 of the Milky San Carlos, in Quevedo, Los Ríos, Ecuador to 73 m in wet-Tropical rainforest. The purpose of this study was to evaluate three planting distances in production clone cacao (Theobroma cacao L.) CCN-51 organic in a triangular double row system. Treatments were distributed in the field under a complete randomized design (CRD) in six replicates. The factor under study consisted of the planting distances: T1. 2m x 3m x 4m, T2. 2.75m x 4m x 2.5m and T3. 3m x 2,5m x 4,0m. To achieve the stated objective incidence broom (Moniliopthora pernicious), the number of healthy and diseased pods, fresh weight in grams, dry cocoa yield in kg ha-1 was evaluated. For statistical analysis of the data analysis of variance (ANOVA) was used and to compare means the Tukey test was applied to 5% probability. As for the results of the experiment the distancing influenced the presence of Witches' broom in that clone cocoa. The lower incidence of this disease presented T2 (2.50mx 2.75mx 4.0m) with 0.17 brooms statistically different from T3 (2.5 mx 3m x 4m) which showed the highest average with 2.0 brooms. In the diseased pods variable in Cocoa clone CCN-51 showed lower incidence T3 (2.5 mx 3m x 4m) with 1.0 this allows us to conclude that a greater distance in the triangular systems, the lower the presence of fungal diseases witch brooms and Monilia. The economic analysis indicated that T2 (2.50mx 2.75mx 4.0m) showed the best performance with 399.43% outperforming all other treatments